Novel PEEK Retentive Elements versus Conventional Retentive Elements in Mandibular Overdentures: A Randomized Controlled Trial - M. Y. Sharaf; Asharaf Eskander; Mohamed Afify (International Journal of Dentistry)
Background. Many patients suffer from lack of retention of conventional mandibular overdentures due to loss of clip retention over time. Computer-aided design-computer-aided manufacturing (CAD-CAM) milled polyether ether ketone (PEEK) materials may be used for the construction of retentive housing and clips for improving retention of implant-supported overdentures. Objective. To compare retention and patient satisfaction of implant-supported mandibular overdentures retained by conventional nylon clip and metal housings for ball attachments versus PEEK clip and housings. Methods. Twenty-two participants were divided into 2 equal groups (n = 11). The conventional group received implant-supported mandibular overdentures retained by metal housings and nylon retentive elements, while the PEEK group received implant-supported mandibular overdentures retained by PEEK retentive elements and housings. The PEEK retentive elements were made using computer-aided design and computer-aided manufacturing (CAD-CAM). The evaluation included measuring the retention by applying a gradual pulling up force by force meter and patient satisfaction with a 7-point visual analog scale (VAS) at overdenture insertion and 3, 6, and 12 months subsequently by a research interviewer. Results. The PEEK group showed statistically significantly increased retention force (P<0.05) at the time of insertion (37.6/17.79) and after 3 months (33.9/16.78), 6 months (32.7/15.97), and 12 months (31.65/13.05). The conventional group had a statistically significantly higher mean overall satisfaction (P<0.05) at the time of insertion (65/82.18). No statistically significant difference was found after 3 months (87.81/84.72). The PEEK group showed statistically significantly higher mean overall satisfaction (P<0.05) after 6 months (86.36/80.18) and 12 months (85.45/79.54). Conclusions. According to the results of this study, the PEEK retentive material provided more retention than did the conventional material and led to improved patient satisfaction. The study was registered at clinical trials.gov (https://clinicaltrials.gov/ct2/show/NCT05079048).